Development of Critical Thinking Instruments and Student Curiosity in Number Theory Course - Zetriuslita; Rezi Ariawan; Damar Rais; Riyan Hidayat (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
This study aims to develop and test the validity and reliability of instruments that can measure critical thinking and curiosity of students in Number Theory course. This research is Research and Development (R&D) with ADDIE model, which consists of 5 stages, namely: analysis, design, development, implementation and evaluation. Data was collected from students who had taken the Number Theory course 40 students and 5 lecturers as expert validators. The instruments developed are in the form of tests and questionnaires consisting of several main indicators for each construct measured. Data collection instruments in the form of critical thinking test validation sheet and curiosity attitude with Likert scale. Data analysis techniques using inferential statistical analysis, namely by testing validity and reliability using the Q-Cochran statistical test . From the results of validation from experts about the validity of the construct and content obtained. The results showed that for construct validity obtained Asymp. Sig = 0.144 greater than α = 0.05, thus H0 is accepted and H1 is rejected and for content validity obtained Asymp. Sig = 0.287 is greater than α = 0.05, thus H0 is accepted and H1 is rejected, it is concluded that the students' mathematical critical thinking instrument is valid. The results of the validity and reliability test to students were obtained. For five test, all of them valid because rxy ≥  rkritis = 0.203. For the reliability of the question, it was obtained R11 = 0.807 and rkritis = 0.203, meaning R11 ≥ rkritis, the conclusion is that the question is reliable and has a very high reliability. For the curiosity questionnaire, the validity of the items by looking at the Corrected Item-Total Correlation. If there is an item whose value is below 0.2, it is said that the item is invalid. Of the 40 items, it can be said that all are valid because the Corrected Item-Total Correlation value is above 0.2 and for reliability, Cronbach's Alpha is obtained at 0.91 ≥ 0.05, which shows that the questionnaire instrument is reliable and has a very high category. The results showed that the critical thinking instrument and curiosity questionnaire are valid and reliable. This instrument can provide information about improving critical thinking skills and curiosity attitudes of students in Number Theory courses and the results can provide a basis for further research on the relationship between critical thinking, curiosity, and learning outcomes in mathematics or other disciplines. Abstrak Penelitian ini bertujuan untuk mengembangkan dan menguji validitas dan reliabilitas instrumen yang dapat mengukur kemampuan berpikir kritis dan rasa ingin tahu mahasiswa pada mata kuliah Teori Bilangan. Penelitian ini merupakan penelitian dan pengembangan (R&D) dengan model ADDIE, yang terdiri dari 5 tahap, yaitu: analisis, desain, pengembangan, implementasi, dan evaluasi. Data dikumpulkan dari mahasiswa yang telah mengambil mata kuliah Teori Bilangan sebanyak 40 mahasiswa dan 5 orang dosen sebagai validator ahli . Instrumen yang dikembangkan berupa tes dan angket yang terdiri dari beberapa indikator utama untuk setiap konstruk yang diukur. Instrumen pengumpulan data berupa lembar validasi tes kemampuan berpikir kritis dan angket sikap rasa ingin tahu dengan skala Likert. Teknik analisis data menggunakan analisis statistik inferensial, yaitu dengan melakukan uji validitas dan reliabilitas dengan menggunakan uji statistik Q-Cochran Hasil penelitian menunjukkan bahwa untuk validitas konstruk diperoleh nilai Asymp. Sig = 0,144 lebih besar dari α = 0,05, dengan demikian H0 diterima dan H1 ditolak dan untuk validitas isi diperoleh nilai Asymp. Sig = 0,287 lebih besar dari α = 0,05, dengan demikian H0 diterima dan H1 ditolak, maka disimpulkan bahwa instrumen berpikir kritis matematis siswa valid. Untuk reliabilitas soal diperoleh R11 = 0,807 dan rkritis = 0,203, berarti R11 ≥ rkritis, kesimpulannya soal tersebut reliabel dan memiliki reliabilitas yang sangat tinggi. Untuk kuesioner rasa ingin tahu, validitas item dengan melihat Corrected Item-Total Correlation. Jika ada item yang nilainya di bawah 0,2 maka dikatakan item tersebut tidak valid. Dari 40 item, dapat dikatakan semua valid karena nilai Corrected Item-Total Correlation di atas 0,2 dan untuk reliabilitas diperoleh Cronbach's Alpha sebesar 0,91 ≥ 0,05 yang menandakan bahwa instrumen kuesioner tersebut reliabel dan memiliki kategori sangat tinggi.Hasil penelitian menunjukkan bahwa instrumen berpikir kritis dan kuesioner curiosity  adalah valid dan reliabel dan dapat digunakan dalam mata kuliah teori bilangan. Hasil penelitian ini dapat menjadi dasar untuk penelitian lebih lanjut mengenai hubungan antara berpikir kritis, curiosity, dan hasil belajar matematika atau disiplin ilmu lainnya.